Mengembangkan Kemampuan Emosional Anak Melalui Kegiatan Pembiasaan Sabar Menunggu Giliran - Tihnike, Dona; Farida, Hikmatul (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The culture of patiently waiting for one's turn is very important for young children. Through repeated and continuous habituation it can foster a culture of patience and discipline. Discipline is one aspect of development that can be improved through a culture of patiently waiting for one's turn. This research is qualitative research, taking a class setting in the Masyitho Glagasari Sukorejo Study Group. Data collection was carried out by conducting observations on students in the study group, interviews with school principals, educators, parents and documentation in the Masyitho Glagasari Sukorejo Study Group. The results of this research show: The cultivation of the habit of patiently waiting for one's turn carried out in the Masyitho Glagasari Sukorejo Study Group is optimal. The school and educators always make it a habit to wait patiently for their turn from when students enter school until when students leave school. Instilling the habit of patiently waiting for your turn to develop children's emotional abilities carried out by educators includes: (a) learning methods (role play, visualization and picture stories, (b) activities to strengthen the culture of queuing, (c) example and supervision (d) agreement, where educators and students make an agreement before learning begins, (e) parental involvement.